Sistem Informasi Manajemen Data Perikanan Tangkap Berbasis Web untuk Meningkatkan Pelayanan Administrasi pada Dinas Perikanan Kabupaten Flores Timur - Ahmad Bapala Sarabiti; Bernadete Deta; Martinus Irwanto Ishak (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The management of capture fisheries data at the Fisheries Office of East Flores Regency is still carried out manually, resulting in delays in data processing, duplicate records, and inefficient report generation. This study aims to design and implement a web-based Capture Fisheries Data Management Information System to improve the effectiveness of data management. The system was developed using the Waterfall model and implemented with PHP, CodeIgniter 4, and MySQL, while system functionality was evaluated through Black Box Testing. The results indicate that the system is capable of managing fishermen, fishing fleet, and fisheries production data in an integrated manner while generating reports quickly and accurately. The testing results demonstrate that all system functions operate according to user requirements. The implementation of the system has improved data management efficiency, reduced recording errors, and supported information presentation and decision-making processes at the Fisheries Office of East Flores Regency.